Fluorescence Studies of Salicylic Acid in Solution and Polymer Film - P. PATIL, MADHAVI; L. BHATTAR, SWAMINATH; R. PATIL, SHIVAJIRAO (Asian Journal of Chemistry, 2010)
Fluorescence of salicylic acid in solution of solvents of different polarity and in polymer matrix is studied to investigate its existence in various geometrical and aggregated forms. The different spectral regions observed in the fluorescence spectra of salicylic acid solutions are explained by the mechanism of formation of salicylic acid anion, zwitter ion and intermolecular hydrogen bonded dimer in the excited state. The transparent salicylic acid doped polymer films prepared from these solutions exhibited nearly identical emission regions in the fluorescence spectra due to formation of similar species in the excited state. The formation of salicylic acid species is further confirmed by lifetimes measured at their respective emission wavelengths. The different values of lifetimes indicate the existence of salicylic acid as different species. The blue emitting salicylic acid doped polymer films are suitable for use in fabrication of organic light emitting devices and also for sunscreen protector films.